Pembuatan Arang Aktif dari Pelepah Sawit Menggunakan Aktivator H2SO4 sebagai Adsorben untuk Pemurnian Air Sungai Siak - Fithry, Dwi Annisa; Nabila, Roida; Ermal, Dini Aulia Sari; Rahmi, Viona Aulia; Jusnita, Jusnita; Parmanoan, Durain (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Oil palm fronds are an agricultural waste with potential application as a raw material for activated carbon due to their lignocellulosic content, which includes cellulose, hemicellulose, and lignin, enabling their function as an adsorbent. In this study, oil palm fronds were carbonized by pyrolysis at a temperature of 350°C, size-reduced to 100 mesh, and subsequently activated using a 0.1 M H₂SO₄ solution for 3 hours, then drying by oven at 70°C. 100 mL of the Siak River sample was added with 3 grams of activated carbon for the adsorption process, then shaken every 20 minutes for 3 hours. Turbidity analysis was conducted using a turbidimeter. The results indicated that the lowest turbidity values were obtained in the morning, namely 16.8 NTU at the upper section and 21.7 NTU at the lower section. This is attributed to the minimal level of community activities around the Siak River during the morning period.